Frequency of Bilateral Hypertrophic Olivary Degeneration in a Large Retrospective Cohort. Issue 2 (9th April 2014) - Carr, Carrie M.; Hunt, Christopher H.; Kaufmann, Timothy J.; Kotsenas, Amy L.; Krecke, Karl N.; Wood, Christopher P.
ABSTRACT BACKGROUND AND PURPOSE Hypertrophic olivary degeneration (HOD) is an uncommon type of transneuronal degeneration. Case reports and case series described in the literature provide a foundation of our current knowledge of HOD. These reports have described HOD most frequently to be unilateral and occurring in association with lesions in the dentato‐rubro‐olivary pathway. Our purpose was to evaluate the rate of bilateral versus unilateral HOD in a large case series. METHODS A retrospective review was performed to identify patients in which the phrase "hypertrophic olivary degeneration" occurred in the radiology report. A diagnosis of HOD was confirmed on imaging if there was focal hyperintensity on T2‐weighted images confined to either or both inferior olivary nuclei. RESULTS A total of 102 patients had findings consistent with HOD. Of these, 76% had findings bilaterally. In 44%, a lesion could not be identified to explain HOD. Bilateral HOD was common in both lesional and nonlesional group, though more common in the nonlesional group. CONCLUSION This study demonstrates that HOD is frequently bilateral. In slightly over 50% of patients with HOD, a lesion can be identified. In just under 50% patients with HOD, a lesion could not be identified and in these cases HOD was present bilaterally in the majority.